The Thrombospondin-1 Mimetic ABT-510 Increases the Uptake and Effectiveness of Cisplatin and Paclitaxel in a Mouse Model of Epithelial Ovarian Cancer - Nicole E. Campbell; James Greenaway; Jack Henkin; Roger A. Moorehead; Jim Petrik (Neoplasia: An International Journal for Oncology Research, 2010)
Epithelial ovarian cancer (EOC) comprises approximately 90% of ovarian cancers and arises from the surface epithelium. Typical treatment of EOC involves cytoreductive surgery combined with chemotherapy. More recent therapies have targeted the tumor vasculature using antiangiogenic compounds such as thrombospondin-1 (TSP-1). TSP-1 mimetic peptides such as ABT-510 have been created and have been in various clinical trials. We have previously shown that ABT-510 reduces abnormal vasculature associated with tumor tissue and increases the presence of mature blood vessels. It has been hypothesized that treatment with antiangiogenic compounds would allow increased delivery of cytotoxic agents and enhance treatment. In this study, we evaluated the potential role of ABT-510 and various chemotherapeutics (cisplatin and paclitaxel) on tumor progression, angiogenesis, and the benefits of combinational treatments on tissue uptake and perfusion using an orthotopic syngeneic mouse model of EOC. Animals were treated with ABT-510 (100 mg/kg per day) alone or in combination with cisplatin (2 mg/kg per 3 days) or paclitaxel (10 mg/kg per 2 days) at 60 days after tumor induction. Radiolabeled and fluorescently labeled paclitaxel demonstrated a significant increase in tumor uptake after ABT-510 treatment. Combined treatment with ABT-510 and cisplatin or paclitaxel resulted in a significant increase in tumor cell and tumor endothelial cell apoptosis and a resultant decrease in ovarian tumor size. Combined treatment also regressed secondary lesions and eliminated the presence of abdominal ascites. The results from this study show that through vessel normalization, ABT-510 increases uptake of chemotherapy drugs and can induce regression of advanced ovarian cancer.